1989
DOI: 10.1523/jneurosci.09-12-04101.1989
|View full text |Cite
|
Sign up to set email alerts
|

The firing of hippocampal place cells predicts the future position of freely moving rats

Abstract: Direct observation and automatic, video-based methods reveal that a large fraction of hippocampal pyramidal neurons recorded from freely moving rats behave as "place cells"; the firing of each place cell occurs almost exclusively when the rat is in a restricted part of its current environment. In earlier work, 2-dimensional firing distributions for place cells over the apparatus area were made under the assumption that the correct location for each spike was the animal's position at the instant that the spike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
214
1
7

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(228 citation statements)
references
References 15 publications
6
214
1
7
Order By: Relevance
“…(6) Coherence is a nearest-neighbor 2-D autocorrelation of firing rate (Muller and Kubie 1989) and is calculated in three steps. First, parallel lists are constructed for the firing rate in each pixel and the average firing rate in the eight nearest neighbors; the average is the sum of the number of spikes in the neighbors divided by the sum of the time spent in the neighbors.…”
Section: Methodsmentioning
confidence: 99%
“…(6) Coherence is a nearest-neighbor 2-D autocorrelation of firing rate (Muller and Kubie 1989) and is calculated in three steps. First, parallel lists are constructed for the firing rate in each pixel and the average firing rate in the eight nearest neighbors; the average is the sum of the number of spikes in the neighbors divided by the sum of the time spent in the neighbors.…”
Section: Methodsmentioning
confidence: 99%
“…Only firing rate distributions with z info Ͼ 1.65 (less than 5% likely to come from the chance distribution) were considered to be location specific. Patchiness measures the global smoothness of a firing rate pattern (20). It is calculated as the number of contiguous regions (patches) in the highest firing rate category (purple) of the firing rate map.…”
Section: Methodsmentioning
confidence: 99%
“…It is calculated as the number of contiguous regions (patches) in the highest firing rate category (purple) of the firing rate map. Spatial coherence measures the local smoothness of a firing rate pattern (20) and is calculated as the z-transform of the correlation between the rate in a pixel and the mean rate in the immediately neighboring pixels.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been suggested that the backward expansion phenomenon may contribute to the transformation of a rate code to a temporal code such as that illustrated in phase precession (Mehta et al, 2002). Perhaps, the backward expansion phenomenon could help to explain other place field phenomenon such as the tendency for place cells to fire in anticipation of entering a specified location within a familiar environment (Muller and Kubie, 1989).…”
Section: Hierarchically Organized Context Processing Within Hippocampusmentioning
confidence: 99%
“…earlier example of prospective coding by place cells was the demonstration that place fields seemed to anticipate the future location of an animal by some 90 ms (Muller and Kubie, 1989). The time scales for the latter two studies are very different so it remains to be determined if they are derived from the same or different mechanism.…”
Section: Hierarchically Organized Context Processing Within Hippocampusmentioning
confidence: 99%